Future of Agrivoltaic projects: A review from the technological forecasting perspective - Leticia Pekk; Petar Sabev Varbanov; Ting Pan; Zoltan Weltsch; Bernadett Radli-Burjan; Andras Hary; Xue-Chao Wang (Cleaner Engineering and Technology)
Agrivoltaic systems integrate photovoltaic (PV) energy generation with agricultural production, creating synergies that enhance land-use efficiency and environmental sustainability. This article reviews agrivoltaic technologies to identify key trends and the most promising future research and development directions. The method applied involves selecting and analysing relevant literature sources and filtering them with regard to the essential questions that need to be answered for the climates of Central Europe and China. These include global development, current applications, and technological progress. The analysis reveals growing attention to system design, performance optimisation, and crop compatibility. Innovations such as bifacial and spectrally selective PV modules boost energy yields while maintaining suitable conditions for shade-tolerant crops like leafy greens and berries.The analysis confirmed the high potential of sustainability benefits (societal, economic, and environmental) and revealed the need for systematic investigations of significant performance factors, including location and system design. A relatively underinvestigated factor is the protection of crops from excessive sunlight, which has become increasingly important. The modelling and optimisation of system operation is also necessary to provide decision-makers with robust tools for project assessment. A roadmap is proposed to guide future research and development.